Parenting, mental health and economic pathways to prevention of violence against children in South Africa - Cluver, L; Shenderovich, Y; Meinck, F; Berezin, M; Doubt, J; Ward, C; Parra-Cardona, J; Lombard, C; Lachman, J; Wittesaele, C; Wessels, I; Gardner, F; et al. (Elsevier, 2020)
Background Parenting programs based on social learning theory have increasing empirical evidence for reducing violence against children. Trials are primarily from high-income countries and with young children. Globally, we know little about how parenting programs work to reduce violence, with no known studies in low or middle-income countries (LMICs). This study examines mechanisms of change of a non-commercialized parenting program, Parenting for Lifelong Health for Teens, designed with the World Health Organization and UNICEF. A cluster randomized trial showed main effects on parenting and other secondary outcomes. We conducted secondary analysis of trial data to investigate five potential mediators of reduced violence against children: improved parenting, adolescent behaviour, caregiver mental health, alcohol/drug avoidance, and family economic strengthening.